2022
DOI: 10.1186/s12871-022-01877-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dexmedetomidine versus fentanyl as adjuvants to bupivacaine in ultrasound-guided transversus abdominis plane block in patients undergoing radical cystectomy: a prospective randomised study

Abstract: Background Transversus abdominis plane (TAP) block is beneficial for pain management after conducting abdominal surgery. Objective To compare the outcomes of dexmedetomidine and fentanyl, as adjuvants to bupivacaine, for ultrasound-guided TAP block analgesia among patients undergoing radical cystectomy for postoperative pain management. Methods This prospective, randomised, comparative study included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This study selection process is summarized in the PRISMA flow chart ( Figure 1 ). According to Cochrane’s Risk of Bias 2 (RoB2) assessment, seventeen RCTs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] were considered to be low-risk and three RCTs [ 30 , 31 , 32 ] had some concerns. Moreover, the quality of the included studies is summarized in Supplementary Materials (Table S2) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study selection process is summarized in the PRISMA flow chart ( Figure 1 ). According to Cochrane’s Risk of Bias 2 (RoB2) assessment, seventeen RCTs [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] were considered to be low-risk and three RCTs [ 30 , 31 , 32 ] had some concerns. Moreover, the quality of the included studies is summarized in Supplementary Materials (Table S2) .…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of those studies concluded that sufentanil consumption was significantly lower in the dexmedetomidine group (SMD = −1.34 [95% CI −2.29 to −0.40], p = 0.005, I2 = 84%, random effects) ( Figure 2 ). Similar to the breast cancer and abdominal surgery, in thoracic cancer [ 28 ] and radical cystectomy [ 32 ], dexmedetomidine adjuvant use decreased the need for analgesic consumption.…”
Section: Resultsmentioning
confidence: 99%
“…18 Adjuvants to bupivacaine such as steroids, alpha-2 agonists, and opioids have been used for TAP blocks to prolong the duration of analgesia with varying durations of clinical efficacy. [20][21][22][23][24][25][26] In a recent retrospective study investigating the use of TAP blocks for chronic abdominal pain, Abd-Elsayed et al identified that patients experienced prolongation of analgesia when steroids were mixed with bupivacaine. 24,26 Additionally, a meta-analysis including nine prospective trials identified that dexamethasone added to local anesthetics in TAP blocks was associated with decreased levels of pain intensity 12 h after surgery however these differences did not remain persistent 24 h following the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal analgesic strategies are continuing to evolve; incorporating opioid sparing techniques and the use of TAP blocks with local anesthetics 18 . Adjuvants to bupivacaine such as steroids, alpha‐2 agonists, and opioids have been used for TAP blocks to prolong the duration of analgesia with varying durations of clinical efficacy 20–26 . In a recent retrospective study investigating the use of TAP blocks for chronic abdominal pain, Abd‐Elsayed et al.…”
Section: Discussionmentioning
confidence: 99%
“…Effects on the cardiac dynamic in dairy calves were previously explored by Cagnardi et al [ 21 ], who demonstrated that injecting 5 µg/kg dexmedetomidine intravenously (IV) resulted in HR reduction. In our case, the authors chose to add 1 µg/mL as an adjuvant to the local anesthetic mixture to improve the overall analgesic effects as performed in other species [ 22 24 ]. Nevertheless, systemic absorption of this drug cannot be excluded entirely, as well as a systemic effect.…”
Section: Discussionmentioning
confidence: 99%